Highly flexible and fold-resistant mesh conveyor belt and its preparation process
By forming a protective layer on the glass fiber mesh and using composite rubber and other raw materials, the problem of insufficient fold resistance of existing high wear-resistant conveyor belt cover rubber is solved, and the preparation of high-flexible fold-resistant grid conveyor belts is realized, which improves its mechanical and temperature resistance, extends its service life and reduces costs.
Patent Information
- Application Number
- CN202510237603.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The folding resistance of the existing high wear-resistant conveyor belt cover glue is insufficient, and further improvement is needed to improve the flexibility and folding resistance of the conveyor belt.
The protective layer on the glass fiber web is formed through specific kneading and vulcanization treatment to improve the high flexibility and fold resistance of the conveyor belt.
The high-flexible fold-resistant grid conveyor belt is achieved, with excellent mechanical properties and temperature resistance, extending the service life of the conveyor belt, reducing the replacement frequency, saving costs, and improving production efficiency.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conveyor belt production, in particular to a highly flexible, fold-resistant grid conveyor belt and a preparation process thereof. Background Art
[0002] Conveyor belts are widely used in industries such as food, environmental protection, printing and dyeing, clothing, chemicals, glass, medicine, electronics, insulation, grinding wheel slicing, machinery, electricity, metallurgy, building materials, and papermaking. They carry the function of conveying materials over long distances, large spans, large volumes, and at high speeds. As a convenient means of transporting materials, conveyor belts are widely used in various industries because of their convenience, efficiency, and labor saving. The current Teflon mesh conveyor belt is made of glass fiber mesh as the base material and coated with Teflon resin to form a Teflon mesh conveyor belt, which is widely used in various industries.
[0003] In the patent document with application number "CN202 21 1583191.X" and name "High wear-resistant conveyor belt covering rubber and preparation method thereof", it is recorded that "the formula ratio is calculated by weight: 100 parts of rubber, 45~65 parts of reinforcing agent, 1~5 parts of nano zinc oxide, 0.5~3 parts of stearic acid, 2~5 parts of antioxidant, 0.1~1 parts of sulfur, and 2~5 parts of accelerator; the above raw materials are subjected to one-stage mixing, two-stage mixing and vulcanization pressing to obtain high wear-resistant conveyor belt covering rubber. The high wear-resistant conveyor belt covering rubber of the present invention is applied to fabric core and steel wire rope core conveyor belts, so that the conveyor belt products have excellent wear resistance while maintaining good physical and mechanical properties, can greatly extend the service life of the conveyor belt, reduce the replacement frequency, save costs and improve production efficiency."
[0004] Although the covering rubber produced by the above patent document can be used for the preparation of conveyor belts, its own folding resistance is relatively insufficient and still needs further improvement. Based on this, the present invention provides a highly flexible folding-resistant mesh conveyor belt material and its preparation process to solve the above technical problems! Summary of the invention
[0005] The purpose of the present invention is to provide a highly flexible and fold-resistant mesh conveyor belt and a preparation process thereof. The prepared highly flexible and fold-resistant mesh conveyor belt not only has good high flexibility and folding resistance, but also has excellent mechanical properties and temperature resistance, effectively ensuring its quality.
[0006] To achieve the above object, the present invention provides the following technical solutions: The first aspect of the present invention provides a highly flexible, fold-resistant mesh conveyor belt, comprising a glass fiber mesh and a protective layer arranged on the glass fiber mesh, wherein the protective layer is composed of the following raw materials in parts by weight: 100 to 120 parts of composite rubber, 3 to 6 parts of functional filler, 3 to 5 parts of stearic acid, 2 to 4 parts of dibenzothiazole disulfide, 4 to 7 parts of synergistic aid, 6 to 10 parts of paraffin, 3 to 5 parts of cross-linking agent and 2 to 5 parts of antioxidant 1010.
[0007] The present invention is further configured as follows: the composite rubber is formed by mixing butadiene rubber, nitrile rubber and polyisoprene rubber in a mass ratio of 1:0.22-0.32:0.12-0.22.
[0008] The present invention is further configured as follows: the preparation process of the functional filler is as follows: The modified nano-silica was placed in an ethanol solution with a concentration of 45-55% at a dosage ratio of 0.008-0.06 g / mL and ultrasonically treated for 20-30 min, and then zinc acetylacetonate and ammonia water were added thereto, and the treatment was carried out at 60-64°C and 200-220 r / min for 24-26 h; Then, the mixture is centrifuged at 8000-10000 r / min for 20-26 min, and then dried at 50-60° C. for 12-14 h to obtain a functional filler.
[0009] The present invention is further configured as follows: the addition amount of the zinc acetylacetonate is 1.3-3.3% of the mass of the modified nano-silicon dioxide, and the addition amount of the ammonia water is 0.5-1.1% of the mass of the modified nano-silicon dioxide.
[0010] The present invention is further configured as follows: the preparation process of the modified nano-silicon dioxide is as follows: The nano-silicon dioxide is placed in a composite solvent at a dosage ratio of 0.02 to 0.12 g / mL and ultrasonically treated for 20 to 30 minutes, and carbon disulfide is added thereto at a weight ratio of 0.3 to 0.8% of the mass of the nano-silicon dioxide, and the mixture is heated to 48 to 52°C and treated at 160 to 200 r / min for 20 to 24 hours; After filtration, the filter cake is washed with anhydrous ethanol and deionized water for 2 to 4 times, and then placed in a vacuum drying oven at 50 to 60° C. for 12 to 14 hours to obtain modified nano-silicon dioxide.
[0011] The present invention is further configured as follows: the composite solvent is formed by mixing anhydrous ethanol, ammonia water and deionized water in a mass ratio of 0.2-0.3:0.1-0.3:1.
[0012] The present invention is further configured as follows: the preparation process of the synergistic aid is as follows: The carbon nanospheres are placed in concentrated sulfuric acid with a concentration of 98% at a dosage ratio of 0.02 to 0.14 g / mL, treated at 55 to 60° C. for 200 to 220 min, filtered, washed with deionized water for 2 to 4 times, and then treated at 70 to 80° C. for 5 to 7 h to obtain a first filler; The first filler is placed in N,N-dimethylformamide at a dosage ratio of 0.02-0.22 g / mL and ultrasonically treated for 20-30 min, and then 0.1-0.5% of the mass of the first filler is added thereto, and the temperature is raised to 72-76° C. and treated for 24-26 h. After filtration, the filler is washed with anhydrous ethanol and deionized water for 2-4 times, and then treated at 70-80° C. for 5-7 h to obtain a second filler; The second filler is placed in tetrahydrofuran at a dosage ratio of 0.03-0.13 g / mL and ultrasonically treated for 20-30 minutes, and then silicon carbide fiber is added thereto, and treated for 30-33 hours in a nitrogen atmosphere at 65-72° C., filtered, washed with deionized water 2-4 times, and then dried in a vacuum drying oven at 50-60° C. to constant weight to obtain a synergistic additive.
[0013] The present invention is further configured as follows: the added amount of the silicon carbide fiber is 1.5-3.5% of the mass of the second filler.
[0014] The present invention is further configured as follows: the cross-linking agent is selected from any one of N,N'-m-phenylene bismaleimide and triisocyanate.
[0015] The second aspect of the present invention: also provides a preparation process of the above-mentioned highly flexible folding-resistant grid conveyor belt, comprising the following steps: Step 1, accurately weighing the composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010, placing the composite rubber in a mixing device, treating it at 120-140° C. for 150-160 min, then adding the functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 thereto, and continuing to mix and process at a temperature of 150-160° C. to obtain a protective material; Step 2: Add protective material to the molding equipment, place the glass fiber mesh in the protective material, pressurize and vulcanize the material in the molding equipment, and after the material is discharged, go through the inspection and metering packaging process in sequence to obtain a highly flexible and fold-resistant mesh conveyor belt; The pressure of the pressurized vulcanization molding is 5-8 MPa, the temperature of the pressurized vulcanization molding is 150-160° C., and the vulcanization time is set to 30-50 min.
[0016] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 are used as raw materials. The composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 are accurately weighed, and the composite rubber is placed in a mixing device for processing, and then functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 are added thereto, and the refining process is continued to obtain a protective material, and then the protective material is added to the molding equipment, and the glass fiber mesh is placed in the protective material, and pressure vulcanization is performed in the molding equipment. After the material is discharged, it is successively inspected and metered and packaged to obtain a highly flexible and folding-resistant mesh conveyor belt. The highly flexible and folding-resistant mesh conveyor belt prepared by the present invention not only has good high-flexibility and folding resistance, but also has excellent mechanical properties and temperature resistance, which effectively guarantees its quality. The highly flexible, fold-resistant mesh conveyor belt and the preparation process thereof provided by the present invention have broader market prospects and are more suitable for promotion. DETAILED DESCRIPTION
[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0018] Example 1: This example provides a highly flexible, fold-resistant mesh conveyor belt, which includes a glass fiber mesh and a protective layer arranged on the glass fiber mesh, and the protective layer is composed of the following raw materials in parts by weight: 100 parts of composite rubber, 3 parts of functional filler, 3 parts of stearic acid, 2 parts of dibenzothiazole disulfide, 4 parts of synergistic additives, 6 parts of paraffin, 3 parts of cross-linking agent and 2 parts of antioxidant 1010.
[0019] In this embodiment, it should be noted that stearic acid was purchased from Guangzhou Jinqixin Chemical New Materials Co., Ltd., dibenzothiazole disulfide was purchased from Shandong Poly Chemical Co., Ltd., paraffin was purchased from Jinan Woneng New Materials Co., Ltd., and antioxidant 1010 was purchased from Suzhou Yitianli Plastic Co., Ltd.
[0020] The composite rubber is made by mixing butadiene rubber, nitrile rubber and polyisoprene rubber in a mass ratio of 1:0.22:0.12.
[0021] In this embodiment, it should be noted that butadiene rubber was purchased from Mitsui Chemicals (Shandong) Co., Ltd., nitrile rubber was purchased from Guangzhou Jinkai Chemical Co., Ltd., and polyisoprene rubber was purchased from Shandong Xinghai Chemical Co., Ltd.
[0022] The preparation process of functional fillers is as follows: The modified nano-silica was placed in a 45% ethanol solution at a dosage ratio of 0.008 g / mL and ultrasonically treated for 20 min, and then zinc acetylacetonate and ammonia water were added thereto and treated at 60°C and 200 r / min for 24 h. Then, the mixture was centrifuged at 8000-10000 r / min for 20 min, and then dried at 50° C. for 12 h to obtain a functional filler.
[0023] Furthermore, the addition amount of zinc acetylacetonate is 1.3% of the mass of the modified nano-silicon dioxide, and the addition amount of ammonia water is 0.5% of the mass of the modified nano-silicon dioxide.
[0024] Among them, the preparation process of modified nano-silica is as follows: Nano-silica was placed in a composite solvent at a dosage ratio of 0.02 g / mL and subjected to ultrasonic treatment for 20 min, and carbon disulfide (0.3% by mass of the nano-silica) was added thereto, and the temperature was raised to 48°C and the temperature was 160 r / min for 20 h. After filtration, the filter cake was washed twice with anhydrous ethanol and deionized water respectively, and then dried in a vacuum drying oven at 50° C. for 12 h to obtain modified nano-silica.
[0025] Furthermore, the composite solvent is prepared by mixing anhydrous ethanol, ammonia water and deionized water in a mass ratio of 0.2:0.1:1.
[0026] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Aohe New Materials Co., Ltd., and zinc acetylacetonate was purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0027] In addition, the preparation process of the synergist is as follows: The carbon nanospheres were placed in concentrated sulfuric acid with a concentration of 98% at a dosage ratio of 0.02 g / mL, treated at 55° C. for 200 min, filtered, washed twice with deionized water, and then treated at 70° C. for 5 h to obtain a first filler; The first filler was placed in N,N-dimethylformamide at a dosage ratio of 0.02 g / mL and ultrasonically treated for 20 minutes, and then 0.1% of the mass of the first filler was added thereto, phosphorus oxychloride was heated to 72°C and treated for 24 hours, and after filtration, it was washed twice with anhydrous ethanol and deionized water respectively, and then treated at 70°C for 5 hours to obtain a second filler; The second filler was placed in tetrahydrofuran at a dosage ratio of 0.03 g / mL and ultrasonically treated for 20 minutes, and then silicon carbide fiber was added thereto. The mixture was treated in a nitrogen atmosphere at 65° C. for 30 hours. After filtration, the mixture was washed twice with deionized water, and then dried in a vacuum drying oven at 50° C. to constant weight to obtain a synergistic additive.
[0028] Furthermore, the added amount of silicon carbide fiber is 1.5% of the mass of the second filler.
[0029] In this embodiment, it should be noted that the carbon nanospheres were purchased from Suzhou Beike Nanotechnology Co., Ltd., and the silicon carbide fibers were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0030] Wherein, the cross-linking agent is N, N'-m-phenylene bismaleimide.
[0031] In this embodiment, it should be noted that N,N'-m-phenylene bismaleimide was purchased from Hubei Dali Chemical Co., Ltd.
[0032] In addition, this embodiment also provides a preparation process of the above-mentioned highly flexible folding-resistant mesh conveyor belt, comprising the following steps: Step 1: accurately weigh the composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010, and place the composite rubber in a mixing device, treat it at 120° C. for 150 minutes, then add the functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 thereto, and continue to mix and process at a temperature of 150° C. to obtain a protective material; Step 2: Add protective material to the molding equipment, place the glass fiber mesh in the protective material, pressurize and vulcanize the material in the molding equipment, and after the material is discharged, go through the inspection and metering packaging process in sequence to obtain a highly flexible and fold-resistant mesh conveyor belt; The pressure of the pressurized vulcanization molding is 5 MPa, the temperature of the pressurized vulcanization molding is 150° C., and the vulcanization time is set to 30 min.
[0033] Example 2: The preparation process of the highly flexible folding-resistant mesh conveyor belt provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation process of the highly flexible folding-resistant mesh conveyor belt in this example are different; the specific raw material composition and the specific preparation process of the highly flexible folding-resistant mesh conveyor belt in this example are as follows: A highly flexible and fold-resistant mesh conveyor belt, comprising a glass fiber mesh and a protective layer arranged on the glass fiber mesh, wherein the protective layer is composed of the following raw materials in parts by weight: 110 parts of composite rubber, 4 parts of functional filler, 4 parts of stearic acid, 3 parts of dibenzothiazole disulfide, 5 parts of synergist, 8 parts of paraffin, 4 parts of cross-linking agent and 3 parts of antioxidant 1010.
[0034] In this embodiment, it should be noted that stearic acid was purchased from Guangzhou Jinqixin Chemical New Materials Co., Ltd., dibenzothiazole disulfide was purchased from Shandong Poly Chemical Co., Ltd., paraffin was purchased from Jinan Woneng New Materials Co., Ltd., and antioxidant 1010 was purchased from Suzhou Yitianli Plastic Co., Ltd.
[0035] The composite rubber is made by mixing butadiene rubber, nitrile rubber and polyisoprene rubber in a mass ratio of 1:0.27:0.17.
[0036] In this embodiment, it should be noted that butadiene rubber was purchased from Mitsui Chemicals (Shandong) Co., Ltd., nitrile rubber was purchased from Guangzhou Jinkai Chemical Co., Ltd., and polyisoprene rubber was purchased from Shandong Xinghai Chemical Co., Ltd.
[0037] The preparation process of functional fillers is as follows: The modified nano-silica was placed in a 50% ethanol solution at a dosage ratio of 0.05 g / mL and ultrasonically treated for 25 min, then zinc acetylacetonate and ammonia water were added thereto and treated at 62°C and 210 r / min for 25 h. Then, the mixture was centrifuged at 9000 r / min for 23 min and dried at 55° C. for 13 h to obtain a functional filler.
[0038] Furthermore, the addition amount of zinc acetylacetonate is 2.3% of the mass of the modified nano-silicon dioxide, and the addition amount of ammonia water is 0.8% of the mass of the modified nano-silicon dioxide.
[0039] Among them, the preparation process of modified nano-silica is as follows: Nano-silica was placed in a composite solvent at a dosage ratio of 0.07 g / mL and subjected to ultrasonic treatment for 25 min, carbon disulfide (0.4% by mass of nano-silica) was added thereto, and the temperature was raised to 50°C and the temperature was 180 r / min for 22 h; After filtration, the filter cake was washed three times with anhydrous ethanol and deionized water respectively, and then dried in a vacuum drying oven at 55° C. for 13 h to obtain modified nano-silica.
[0040] Furthermore, the composite solvent is prepared by mixing anhydrous ethanol, ammonia water and deionized water in a mass ratio of 0.3:0.2:1.
[0041] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Aohe New Materials Co., Ltd., and zinc acetylacetonate was purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0042] In addition, the preparation process of the synergist is as follows: The carbon nanospheres were placed in concentrated sulfuric acid with a concentration of 98% at a dosage ratio of 0.08 g / mL, treated at 57° C. for 210 min, filtered, washed with deionized water for 3 times, and then treated at 75° C. for 6 h to obtain a first filler; The first filler was placed in N,N-dimethylformamide at a dosage ratio of 0.12 g / mL and ultrasonically treated for 25 minutes, and then 0.3% of the mass of the first filler was added thereto, phosphorus oxychloride was heated to 74°C and treated for 25 hours, and after filtration, it was washed with anhydrous ethanol and deionized water for 3 times respectively, and then treated at 75°C for 6 hours to obtain a second filler; The second filler was placed in tetrahydrofuran at a dosage ratio of 0.08 g / mL and ultrasonically treated for 25 minutes, and then silicon carbide fiber was added thereto. The mixture was treated in a nitrogen atmosphere at 68° C. for 31 hours. After filtration, the mixture was washed with deionized water for 3 times, and then dried in a vacuum drying oven at 55° C. to constant weight to obtain a synergistic additive.
[0043] Furthermore, the added amount of silicon carbide fiber is 2.5% of the mass of the second filler.
[0044] In this embodiment, it should be noted that the carbon nanospheres were purchased from Suzhou Beike Nanotechnology Co., Ltd., and the silicon carbide fibers were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0045] Wherein, triisocyanate is selected as the cross-linking agent.
[0046] In this embodiment, it should be noted that the triisocyanate was purchased from Kandis Chemical (Hubei) Co., Ltd.
[0047] In addition, this embodiment also provides a preparation process of the above-mentioned highly flexible folding-resistant mesh conveyor belt, comprising the following steps: Step 1, accurately weighing the composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010, and placing the composite rubber in a mixing device, treating it at 130° C. for 155 minutes, then adding the functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 thereto, and continuing to open the mixing process at a temperature of 155° C. to obtain a protective material; Step 2: Add protective material to the molding equipment, place the glass fiber mesh in the protective material, pressurize and vulcanize the material in the molding equipment, and after the material is discharged, go through the inspection and metering packaging process in sequence to obtain a highly flexible and fold-resistant mesh conveyor belt; The pressure of the pressurized vulcanization molding is 6 MPa, the temperature of the pressurized vulcanization molding is 155° C., and the vulcanization time is set to 40 min.
[0048] Example 3: The preparation process of the highly flexible folding-resistant mesh conveyor belt provided in this example is basically the same as that in Example 1, except that: the specific raw material composition and the specific preparation process of the highly flexible folding-resistant mesh conveyor belt in this example are different; the specific raw material composition and the specific preparation process of the highly flexible folding-resistant mesh conveyor belt in this example are as follows: A highly flexible and fold-resistant mesh conveyor belt, comprising a glass fiber mesh and a protective layer arranged on the glass fiber mesh, wherein the protective layer is composed of the following raw materials in parts by weight: 120 parts of composite rubber, 6 parts of functional filler, 5 parts of stearic acid, 4 parts of dibenzothiazole disulfide, 7 parts of synergistic additive, 10 parts of paraffin, 5 parts of cross-linking agent and 5 parts of antioxidant 1010.
[0049] In this embodiment, it should be noted that stearic acid was purchased from Guangzhou Jinqixin Chemical New Materials Co., Ltd., dibenzothiazole disulfide was purchased from Shandong Poly Chemical Co., Ltd., paraffin was purchased from Jinan Woneng New Materials Co., Ltd., and antioxidant 1010 was purchased from Suzhou Yitianli Plastic Co., Ltd.
[0050] The composite rubber is made by mixing butadiene rubber, nitrile rubber and polyisoprene rubber in a mass ratio of 1:0.32:0.22.
[0051] In this embodiment, it should be noted that butadiene rubber was purchased from Mitsui Chemicals (Shandong) Co., Ltd., nitrile rubber was purchased from Guangzhou Jinkai Chemical Co., Ltd., and polyisoprene rubber was purchased from Shandong Xinghai Chemical Co., Ltd.
[0052] The preparation process of functional fillers is as follows: The modified nano-silica was placed in a 55% ethanol solution for ultrasonic treatment for 30 min at a dosage ratio of 0.06 g / mL, and then zinc acetylacetonate and ammonia water were added thereto and treated at 64°C and 220 r / min for 26 h. Then, the mixture was centrifuged at 10000 r / min for 26 min, and then dried at 60° C. for 14 h to obtain a functional filler.
[0053] Furthermore, the addition amount of zinc acetylacetonate is 3.3% of the mass of the modified nano-silicon dioxide, and the addition amount of ammonia water is 1.1% of the mass of the modified nano-silicon dioxide.
[0054] Among them, the preparation process of modified nano-silica is as follows: Nano-silica was placed in a composite solvent at a dosage ratio of 0.12 g / mL and subjected to ultrasonic treatment for 30 min, carbon disulfide (0.8% by mass of nano-silica) was added thereto, and the temperature was raised to 52°C and the temperature was 200 r / min for 24 h; After filtration, the filter cake was washed four times with anhydrous ethanol and deionized water respectively, and then dried in a vacuum drying oven at 60° C. for 14 h to obtain modified nano-silica.
[0055] Furthermore, the composite solvent is prepared by mixing anhydrous ethanol, ammonia water and deionized water in a mass ratio of 0.3:0.3:1.
[0056] In this embodiment, it should be noted that nano-silicon dioxide was purchased from Shijiazhuang Aohe New Materials Co., Ltd., and zinc acetylacetonate was purchased from Wuhan Shuer Biotechnology Co., Ltd.
[0057] In addition, the preparation process of the synergist is as follows: The carbon nanospheres were placed in concentrated sulfuric acid with a concentration of 98% at a dosage ratio of 0.14 g / mL, treated at 60° C. for 220 min, filtered, washed with deionized water for 4 times, and then treated at 80° C. for 7 h to obtain a first filler; The first filler was placed in N,N-dimethylformamide at a dosage ratio of 0.22 g / mL and ultrasonically treated for 30 minutes, and then 0.5% of the mass of the first filler was added thereto, phosphorus oxychloride was heated to 76°C and treated for 26 hours, and after filtration, it was washed with anhydrous ethanol and deionized water for 4 times respectively, and then treated at 80°C for 7 hours to obtain a second filler; The second filler was placed in tetrahydrofuran at a dosage ratio of 0.13 g / mL and ultrasonically treated for 20 to 30 minutes, and then silicon carbide fiber was added thereto. The mixture was treated in a nitrogen atmosphere at 72° C. for 33 hours. After filtration, the mixture was washed with deionized water for 4 times, and then dried in a vacuum drying oven at 60° C. to constant weight to obtain a synergistic additive.
[0058] Furthermore, the added amount of silicon carbide fiber is 3.5% of the mass of the second filler.
[0059] In this embodiment, it should be noted that the carbon nanospheres were purchased from Suzhou Beike Nanotechnology Co., Ltd., and the silicon carbide fibers were purchased from Shanghai Xiangtian Nanomaterials Co., Ltd.
[0060] The cross-linking agent is selected from any one of N,N'-m-phenylene bismaleimide and triisocyanate.
[0061] In this embodiment, it should be noted that N,N'-m-phenylene bismaleimide was purchased from Hubei Dali Chemical Co., Ltd., and triisocyanate was purchased from Kangdisi Chemical (Hubei) Co., Ltd.
[0062] In addition, this embodiment also provides a preparation process of the above-mentioned highly flexible folding-resistant mesh conveyor belt, comprising the following steps: Step 1, accurately weighing the composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010, placing the composite rubber in a mixing device, treating it at 140° C. for 160 min, then adding the functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 thereto, and continuing to mix and process at a temperature of 160° C. to obtain a protective material; Step 2: Add protective material to the molding equipment, place the glass fiber mesh in the protective material, pressurize and vulcanize the material in the molding equipment, and after the material is discharged, go through the inspection and metering packaging process in sequence to obtain a highly flexible and fold-resistant mesh conveyor belt; The pressure of the pressurized vulcanization molding is 8 MPa, the temperature of the pressurized vulcanization molding is 160° C., and the vulcanization time is set to 50 min.
[0063] Comparative Example 1: The difference from Example 1 is that an equal amount of silicon dioxide is used to replace the functional filler in this example.
[0064] Comparative Example 2: The difference from Example 1 is that in this example, an equal amount of silicon carbide fiber is used to replace the synergistic aid.
[0065] Performance test: The samples of highly flexible and fold-resistant mesh conveyor belts provided in Examples 1 to 3 and Comparative Examples 1 to 2 are marked as Examples 1 to 3 and Comparative Examples 1 to 2, respectively; and the relevant properties of the highly flexible and fold-resistant mesh conveyor belts provided in Examples 1 to 3 and Comparative Examples 1 to 2 are tested as follows: 1. Tensile strength and elongation at break test: Test according to the testing standard of GB / T1040.2-2006.
[0066] 2. Folding test: Tested according to the testing standard of GB / T3903.1-2017, sample size: 200mm*50mm*20mm, test conditions: flexion angle: 50°, flexion frequency: 230 times / minute, flexion times: 40,000 times, cut length: 5mm.
[0067] 3. Temperature resistance test: After treatment at 145℃×30min, test according to the testing standard of GB / T1040.2-2006.
[0068] The obtained test data are recorded in Table 1 and Table 2 below.
[0069]
[0070]
[0071]
[0072] By comparing and analyzing the relevant data in Tables 1 to 3, it can be seen that the high-flexibility folding-resistant mesh conveyor belt prepared by the present invention not only has good high-flexibility folding-resistant performance, but also has excellent mechanical properties and temperature resistance, effectively ensuring its quality. This shows that the high-flexibility folding-resistant mesh conveyor belt and its preparation process provided by the present invention have a broader market prospect and are more suitable for promotion.
[0073] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0074] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Highly flexible and fold-resistant mesh conveyor belt, characterized in that: The highly flexible and fold-resistant mesh conveyor belt includes a glass fiber mesh and a protective layer arranged on the glass fiber mesh, wherein the protective layer is composed of the following raw materials in parts by weight: 100 to 120 parts of composite rubber, 3 to 6 parts of functional filler, 3 to 5 parts of stearic acid, 2 to 4 parts of dibenzothiazole disulfide, 4 to 7 parts of synergistic additives, 6 to 10 parts of paraffin, 3 to 5 parts of cross-linking agent and 2 to 5 parts of antioxidant 1010.
2. The highly flexible folding-resistant mesh conveyor belt according to claim 1, characterized in that: The composite rubber is prepared by mixing butadiene rubber, nitrile rubber and polyisoprene rubber in a mass ratio of 1:0.22-0.32:0.12-0.
22.
3. The highly flexible folding-resistant mesh conveyor belt according to claim 1, characterized in that: The preparation process of the functional filler is as follows: The modified nano-silica was placed in an ethanol solution with a concentration of 45-55% at a dosage ratio of 0.008-0.06 g / mL and ultrasonically treated for 20-30 min, and then zinc acetylacetonate and ammonia water were added thereto, and the treatment was carried out at 60-64°C and 200-220 r / min for 24-26 h; Then, the mixture is centrifuged at 8000-10000 r / min for 20-26 min, and then dried at 50-60° C. for 12-14 h to obtain a functional filler.
4. The highly flexible folding-resistant mesh conveyor belt according to claim 3, characterized in that: The addition amount of the zinc acetylacetonate is 1.3-3.3% of the mass of the modified nano-silicon dioxide, and the addition amount of the ammonia water is 0.5-1.1% of the mass of the modified nano-silicon dioxide.
5. The highly flexible folding-resistant mesh conveyor belt according to claim 3, characterized in that: The preparation process of the modified nano silicon dioxide is as follows: The nano-silicon dioxide is placed in a composite solvent at a dosage ratio of 0.02 to 0.12 g / mL and ultrasonically treated for 20 to 30 minutes, and carbon disulfide is added thereto at a weight ratio of 0.3 to 0.8% of the mass of the nano-silicon dioxide, and the mixture is heated to 48 to 52°C and treated at 160 to 200 r / min for 20 to 24 hours; After filtration, the filter cake is washed with anhydrous ethanol and deionized water for 2 to 4 times, and then placed in a vacuum drying oven at 50 to 60° C. for 12 to 14 hours to obtain modified nano-silicon dioxide.
6. The highly flexible folding-resistant mesh conveyor belt according to claim 5, characterized in that: The composite solvent is prepared by mixing anhydrous ethanol, ammonia water and deionized water in a mass ratio of 0.2-0.3:0.1-0.3:
1.
7. The highly flexible folding-resistant mesh conveyor belt according to claim 1, characterized in that: The preparation process of the synergistic aid is as follows: The carbon nanospheres are placed in concentrated sulfuric acid with a concentration of 98% at a dosage ratio of 0.02 to 0.14 g / mL, treated at 55 to 60° C. for 200 to 220 min, filtered, washed with deionized water for 2 to 4 times, and then treated at 70 to 80° C. for 5 to 7 h to obtain a first filler; The first filler is placed in N,N-dimethylformamide at a dosage ratio of 0.02-0.22 g / mL and ultrasonically treated for 20-30 min, and then 0.1-0.5% of the mass of the first filler is added thereto, and the temperature is raised to 72-76° C. and treated for 24-26 h. After filtration, the filler is washed with anhydrous ethanol and deionized water for 2-4 times, and then treated at 70-80° C. for 5-7 h to obtain a second filler; The second filler is placed in tetrahydrofuran at a dosage ratio of 0.03-0.13 g / mL and ultrasonically treated for 20-30 minutes, and then silicon carbide fiber is added thereto, and treated for 30-33 hours in a nitrogen atmosphere at 65-72° C., filtered, washed with deionized water 2-4 times, and then dried in a vacuum drying oven at 50-60° C. to constant weight to obtain a synergistic additive.
8. The highly flexible folding-resistant mesh conveyor belt according to claim 7, characterized in that: The added amount of the silicon carbide fiber is 1.5-3.5% of the mass of the second filler.
9. The highly flexible folding-resistant mesh conveyor belt according to claim 1, characterized in that: The cross-linking agent is selected from any one of N,N'-m-phenylene bismaleimide and triisocyanate.
10. The process for preparing the highly flexible and fold-resistant mesh conveyor belt according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, accurately weighing the composite rubber, functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010, placing the composite rubber in a mixing device, treating it at 120-140° C. for 150-160 min, then adding the functional filler, stearic acid, dibenzothiazole disulfide, synergist, paraffin, crosslinking agent and antioxidant 1010 thereto, and continuing to mix and process at a temperature of 150-160° C. to obtain a protective material; Step 2: Add protective material to the molding equipment, place the glass fiber mesh in the protective material, pressurize and vulcanize the material in the molding equipment, and after the material is discharged, go through the inspection and metering packaging process in sequence to obtain a highly flexible and fold-resistant mesh conveyor belt; The pressure of the pressurized vulcanization molding is 5-8 MPa, the temperature of the pressurized vulcanization molding is 150-160° C., and the vulcanization time is set to 30-50 min.
Citation Information
Patent Citations
High-wear-resistance conveyor belt cover rubber and preparation method thereof
CN115785541A
Preparation method of silicon carbide / carbon nano material composite visible-light photocatalyst
CN103878006A
High-strength tear-resistant hangtag and making process thereof
CN110628123A
High-temperature-resistant flame-retardant conveying belt and preparation method thereof
CN118664976A